Hierarchy and the Power-Law Income Distribution Tail - Blair Fix (Journal of Computational Social Science, 2018)
What explains the power-law distribution of top incomes? This paper tests the hypothesis that it is firm hierarchy that creates the power-law income distribution tail. Using the available case-study evidence on firm hierarchy, I create the first large-scale simulation of the hierarchical structure of the US private sector. Although not tuned to do so, this model reproduces the power-law scaling of top US incomes. I show that this is purely an effect of firm hierarchy. This raises the possibility that the ubiquity of power-law income distribution tails is due to the ubiquity of hierarchical organization in human societies.
Additional information: Manuscript Version (Preprint)
Keywords: 330; power law; income distribution; firm hierarchy; economic modeling